2019
DOI: 10.1155/2019/6794837
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clothing on Vitamin D Status, Bone Turnover Markers, and Bone Mineral Density in Young Kuwaiti Females

Abstract: Many Arab women in the Gulf region cover their bodies for cultural and religious reasons, limiting the skin’s exposure to sunlight and therefore its ability to synthesize vitamin D. The aim of this study is to determine whether the clothing style of Kuwaiti premenopausal women affects their vitamin D status, bone marker expression, and bone density. Three groups of healthy unmarried single Kuwaiti females (20-35 years old; n=30 per group) were recruited randomly from the general community: a control group who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 64 publications
(78 reference statements)
0
15
0
1
Order By: Relevance
“…The full body covering practiced by females in many middle eastern countries may be related to the higher rate of vitamin D deficiency observed in these populations and may contribute to the higher rate of MS in female population and in those who report lower sun exposure in these populations. 32,33 Lower sun exposure could also be caused by is the reduced physical activity levels of Middle Eastern populations, consequent to lifestyle changes caused by the rise of industrialization and urbanization. 34 One of the important risk factors addressed in this study was cigarette smoking, which was twice as common among controls.…”
Section: Methodsmentioning
confidence: 99%
“…The full body covering practiced by females in many middle eastern countries may be related to the higher rate of vitamin D deficiency observed in these populations and may contribute to the higher rate of MS in female population and in those who report lower sun exposure in these populations. 32,33 Lower sun exposure could also be caused by is the reduced physical activity levels of Middle Eastern populations, consequent to lifestyle changes caused by the rise of industrialization and urbanization. 34 One of the important risk factors addressed in this study was cigarette smoking, which was twice as common among controls.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D deficiency was found to be prevalent in Kuwaiti women wearing Western and traditional clothing but was more marked in the latter group. ( 157 ) Similarly, hijab‐wearing women in Nova‐Scotia (Canada) had less good vitamin D status than Western‐dressing counterparts. ( 158 ) Another factor to consider is physical activity, which may contribute to better vitamin D status independently of sunlight and dietary intake.…”
Section: Personal Factorsmentioning
confidence: 99%
“…Many studies adopted the lowest conservative ranges for vitamin D3, with a higher set point or physiologic adaptation of vitamin D, which may upregulate PTH [1,3,21,22]. Other studies also reported a non-significant relationship between vitamin D and PTH [7,11,18,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypovitaminosis D is 1.6 to 1.7 times higher for women wearing a hijab and 1.9 to 2.7 times higher for women wearing a niqab than women in western dress styles [ 1 , 6 ]. Hypovitaminosis D carries a greater risk of osteoporosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%